2017
DOI: 10.1080/01426397.2016.1269882
|View full text |Cite
|
Sign up to set email alerts
|

‘This is not the jungle, this is mybarbecho’: semantics of ethnoecological landscape categories in the Bolivian Amazon

Abstract: Through a case study with Spanish-speaking Takana indigenous people in the Bolivian Amazon, we explored ethnoecological landscape categories, including their ecological underpinnings, cultural significance and hierarchical organisation. Using field walks and interviews with consultants, we elicited 156 ethnoecological landscape categories, 60 of which related to vegetation types. However, sorting exercises with landscape photographs revealed that vegetation was not a guiding organisation principle. Takana cons… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(21 citation statements)
references
References 42 publications
0
19
2
Order By: Relevance
“…Consequently, what is not on the map is often also not considered in decision-making, which, if failing to adapt to local understandings can have tangible detrimental impact on the lives of people affected [8]. Although the general belief is that land use maps created through participatory processes better reflect local perceptions and priorities, our results showed that important landscape categories associated with informal land rights and certain behavioral rules [55], for example, mineral salt licks, old fallow plots, or patches of economically important plants, were not represented on sketch maps, and would therefore have been overlooked in a planning process. In fact, a community mapping project in the study area implemented by WCS in collaboration with CIPTA (WCS report, unpublished) resulted in maps that did not contain information on the existence or location of mineral salt licks or other culturally important sites and local land uses.…”
Section: Implications For Using Sketch Maps In Decision-makingcontrasting
confidence: 37%
See 3 more Smart Citations
“…Consequently, what is not on the map is often also not considered in decision-making, which, if failing to adapt to local understandings can have tangible detrimental impact on the lives of people affected [8]. Although the general belief is that land use maps created through participatory processes better reflect local perceptions and priorities, our results showed that important landscape categories associated with informal land rights and certain behavioral rules [55], for example, mineral salt licks, old fallow plots, or patches of economically important plants, were not represented on sketch maps, and would therefore have been overlooked in a planning process. In fact, a community mapping project in the study area implemented by WCS in collaboration with CIPTA (WCS report, unpublished) resulted in maps that did not contain information on the existence or location of mineral salt licks or other culturally important sites and local land uses.…”
Section: Implications For Using Sketch Maps In Decision-makingcontrasting
confidence: 37%
“…The methodology and elicited landscape terms are presented elsewhere in more detail [55]. For comprehensibility, we include here a brief description of the method used.…”
Section: Eliciting Ethnoecological Landscape Categories Through Fieldmentioning
confidence: 99%
See 2 more Smart Citations
“…These knowledge systems express themselves not just in the information that indigenous people hold, for example, about traditional medicinal plants, game species, or climate patterns, but also in their daily practices and in their wider beliefs and worldviews, often termed cosmovision, cosmology, or "kosmos" (Toledo 1992, Toledo andBarrera-Bassols 2009). One important element of indigenous environmental knowledge systems is the classification of habitats, ecosystems, or landscapes (Berkes et al 1998, Omotayo and Musa 1999, Shepard et al 2001, Davidson-Hunt and Berkes 2003, Duvall 2008, Levinson 2008, Johnson and Davidson-Hunt 2011, Molnár 2013, Wartmann and Purves 2018. Such classification systems rely on various indicators to delimit boundaries between spatial units.…”
Section: Introductionmentioning
confidence: 99%